Resistance to cypermethrin and amitraz in Rhipicephalus (Boophilus) microplus on the Santa Catarina Plateau, Brazil - Luana Paula Haubold Neis Veiga (Revista Brasileira de Parasitologia Veterinária, 2012)
With the objective of evaluating Rhipicephalus (Boophilus) microplus resistance to cipermetrina and amitraz, were collected engorged tick females from cattle on 20 farms on the Santa Catarina Plateau, in southern Brazil, between January of 2004 and May of 2006. Were also received 20 groups of engorged R. (B.) microplus females, collected by cattle farmers requesting acaricidal efficacy (AE) testing. Were performed in vitro tests, which consisted of immersing engorged females in cypermethrin (0.015%) and in amitraz (0.025%). An AE ≥95% was considered indicative of effectiveness. Of the 20 collected groups, 18 (90%) showed cypermethrin resistance and 1 (5%) showed amitraz resistance. Of the 20 received groups, 19 (95%) showed cypermethrin resistance and 2 (10%) showed amitraz resistance. The AE of cypermethrin was found to be ≥95%, 85-94%, and 55-64%, respectively, in 4 (57.1%), 2 (28.6%), and 1 (14.3%) of 7 reference groups, collected in the 1997-2001 period. The AE of amitraz was ≥95% in all of those groups. Among the groups of specimens received for analysis in that period, the AE of amitraz was ≥95% in 6 (85.71%) and 75-84% in 1 (14.28%). R. (B.) microplus resistance to acaricides is increasing on the Santa Catarina Plateau.